A construção do conhecimento via Facebook - da Silva, Rodrigo Baez (2016)
This study was to analyze the behavior of third graders - class "A" - the Caetano Pinto State School for teacher's lessons the curriculum component of Geography in Educational Technology Center (STE) across the Facebook social media in building collaborative knowledge. The work is the result of a combination of teaching practice developed in the classroom, by carrying out initiation activities to teaching, for fellows PIBID /EaD / UFGD. The use of social media as an educational resource has been shown to have potential as a learning tool if implemented.